Ślady egzegezy Filona Aleksandryjskiego w "De monastica exercitatione" Nila z Ancyry - Nieścior, Leon (Vox Patrum, 2018)
We encounter in the Nil of Ancyra’s writing De monastica exercitatione at least a dozen instances of the allegorical interpretation of certain places in the Old Testament, where Nil of Ancyra’s exegesis seems to refer to the Philo of Alexandria’s interpretation. In a few places there are significant differences in interpretation, but Nil decisively continues or repeats exegetical ideas of Philo. In two cases, in a longer allegory about Joseph who seeks his brothers and about the ritual washing of the sacrificial calf (De monastica exercitatione 44-45 and 56), the dependence on Philo becomes verbal. The borrowings come most often from Legum allegoriarum libri, which seem to be especially close to Nil. However, the traces of Philo’s exegesis from other writings of the Alexandrian seem to show a wider knowledge of his works by the monk of Ancyra. There is a probability of indirect borrowing and indirect knowledge of Philo’s exegesis by Nil, by other authors, but we find no evidence of such medium. However, for example, Origen’s relationship with Philo in the exegesis of the concerned places is quite loose and does not give grounds for the seeking such medium. The Philo’s ascetic orientation to exegesis, his connection to Greek ethical philosophy, willingness to use the biblical allegory, these and other factors may have influenced Nil to seek inspiration by the Jewish philosopher. The predicted borrowings had also their consequences. The copying Philonian thought led to take over the ideas borrowed by others, including the elements of Platonism and Stoicism.